Pembuatan Biobriket Dari Limbah Sekam Padi Dan Tempurung Kelapa Dengan Perekat Tepung Tapioka - Sofyana Sofyana; Muhammad Iqfal; Muhammad Reza Zuhra (Jurnal Inovasi Ramah Lingkungan, 2021)
One of the problems facing the world today is the supply of fuel oil and gas are dwindling. Rice husk and coconut shell is a potential raw material to be used as an alternative fuel. In this study, rice husks and coconut shells made biobriket with the addition of starch as an adhesive to produce alternative fuels with high calorific value and economic value. This study aimed to determine the effect of authoring and composition ratio of adhesive to produce standards-compliant biobriket SNI. Briquettes made in this study comprises several processes such as: preparation of raw materials, the removal of the water content and size reduction of raw materials, Molding briquettes using a press machine with Biomass and adhesive composition ratio in % (w/w), namely; 97: 3; 95: 5; 93: 7; 90:10; 85:15 with a particle size of 60 mesh material and briquette pressing pressure of 5 tons/cm . Briquette quality testing which includes the heating value, moisture and ash content. The results show biobriket has particularly rice husk ash content of about 17-25%. The water content of about 5-8 % and a calorific value of approximately 4430.94 to 6779.55 cal/g, while the coconut shell biobriket has ash content of about 2-3%. The water content of about 6-9% and a calorific value of approximately 4662.38 to 7016.17 cal/g. In this research biobriket coconut shell in accordance with SNI standards.